2021
DOI: 10.1111/dom.14445
|View full text |Cite
|
Sign up to set email alerts
|

Risk of diabetic macular oedema with sodium‐glucose cotransporter‐2 inhibitors in type 2 diabetes patients: A multi‐institutional cohort study in Taiwan

Abstract: Aims To investigate the risk of diabetic macular oedema (DMO) associated with the use of sodium‐glucose cotransporter‐2 (SGLT2) inhibitors in patients with type 2 diabetes mellitus (T2DM). Materials and Methods We conducted a retrospective cohort study by analysing a large multi‐institutional electronic medical records database in Taiwan. We included adult patients with T2DM without DMO newly receiving either SGLT2 inhibitors or glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) during the period 2016 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…Although some recent clinical studies have reported the beneficial effect of SGLT2i on DR [4,5] and diabetic macular edema [6,7], the EMPA-REG outcome trial could not find a beneficial effect of empagliflozin on DR [8]. Eid et al, reported that the long-term administration of empagliflozin for 10 weeks from 6 to 16 weeks of age did not ameliorate any microvascular complications in db/db mice [19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although some recent clinical studies have reported the beneficial effect of SGLT2i on DR [4,5] and diabetic macular edema [6,7], the EMPA-REG outcome trial could not find a beneficial effect of empagliflozin on DR [8]. Eid et al, reported that the long-term administration of empagliflozin for 10 weeks from 6 to 16 weeks of age did not ameliorate any microvascular complications in db/db mice [19].…”
Section: Discussionmentioning
confidence: 98%
“…These agents are commonly used by young obese patients with type 2 diabetes because weight reduction can be expected as calories are lost when glucose is excreted in the urine [3]. Recently, some clinical case series have shown the beneficial effects of SGLT2i on DR [4,5] and diabetic macular edema [6,7]. However, the EMPA-REG outcome trial could not identify a beneficial effect of empagliflozin on DR [8].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found that ertugliflozin reduced the risk of retinal disease, and empagliflozin reduced the risk of DR compared to control group. A retrospective cohort study conducted by Su et al showed that SGLT-2i reduced the risk of diabetic macular edema (DME) in T2DM patients compared with GLP-1RA, through non-hypoglycemic mechanisms ( 65 ). Similarly, a study on 3 T2DM patients with chronic DME who were refractory to anti-vascular endothelial growth factor (VEGF) therapy and other treatments found that chronic DME improved after using empagliflozin, dapagliflozin, or luseogliflozin.…”
Section: Discussionmentioning
confidence: 99%
“… 49 This action could explain the greater DED risk reduction with SGLT2 inhibitors compared with GLP-1 RAs. Together with the positive findings from previous studies related to different ocular inflammatory diseases (eg, diabetic retinopathy, diabetic macular edema, and glaucoma), 15 , 16 , 17 clinicians may also evaluate the risks for ophthalmologic conditions when selecting antidiabetic medications as intensification therapy to optimize the treatment benefits. Further research should explore the mechanisms of SGLT2 inhibitors in ocular tissues in patients with T2D.…”
Section: Discussionmentioning
confidence: 97%
“…20 The CGRD has been proven to be an important data source to provide real-world evidence in previous comparison studies. 16,17,[21][22][23] The data representativeness and the validity of diagnostic codes in the CGRD have also been validated. 15,16,20,[24][25][26][27] This study protocol was approved, with waiver of informed consent, by the institutional review board of the Chang Gung Medical Foundation, and we followed the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) reporting guideline in the reporting of our results.…”
Section: Introductionmentioning
confidence: 99%